The role of sulfur compounds in chronic obstructive pulmonary disease - Jiang, Simin; Chen, Yahong (Frontiers in Molecular Biosciences, 2022)
Chronic obstructive pulmonary disease (COPD) is a common respiratory disease that brings about great social and economic burden, with oxidative stress and inflammation affecting the whole disease progress. Sulfur compounds such as hydrogen sulfide (H2S), thiols, per sulfides/polysulfides have intrinsic antioxidative and antiinflammation ability, which engaged in the pathophysiological process of COPD. Hydrogen sulfide mainly exhibits its function by S-sulfidation of the cysteine residue of the targeted proteins. It also interacts with nitric oxide, and acts as a potential biomarker for COPD phenotype. Thiols’ redox buffer such as the glutathione redox couple is a major non-enzymatic redox buffer reflecting the oxidative stress in the organism. The disturbance of redox buffers was often detected in patients with COPD and redress the balance could delay COPD exacerbation. Sulfane sulfur refers to a divalent sulfur atom bonded with another sulfur. Amongst them, persulfides and polysulfides have an evolutionarily conserved modification with antiaging effects. Sulfur compounds and their relative signaling pathway are also associated with the development of comorbidities in COPD. Synthetic compounds which can release H2S and persulfides in the organism have gradually been developed. Naturally extracted sulfur compounds with pharmacological effects also aroused great interests. This article discussed the biological functions and mechanism of sulfur compounds in regulating COPD and its comorbidities.